Accuracy of Medical Students in Detecting Pleural Effusion Using Lung Ultrasound as an Adjunct to the Physical Examination. (25th March 2018) - Steinmetz, Peter; Oleskevich, Sharon; Dyachenko, Alina; McCusker, Jane; Lewis, John
Abstract : Objectives: This study compared the accuracy of medical students in identifying pleural effusion in hospitalized patients using the physical examination versus lung ultrasound (US). Methods: Fourth‐year medical students (n = 14) received 20 hours of general practical US training (including 2 hours of specialized lung US training) plus theoretical and video documentation. The students used the physical examination alone versus the physical examination plus lung US to document the presence or absence of pleural effusion in the right and left hemithoraces of hospitalized patients (n = 11 patients; 22 hemithoraces examined 544 times in total). The reference standard for identification of pleural effusion was a lung US examination by 2 expert point‐of‐care sonographers. Results: The odds of correctly identifying the presence versus absence of pleural effusion was 5 times greater with lung US as an adjunct to the physical examination compared to the physical examination alone (odds ratio [OR], 5.1 from multivariate logistic regression; 95% confidence interval, 3.3–8.0). The addition of lung US to the physical examination resulted in an increase in sensitivity from 48% to 90%, in specificity from 73% to 86%, and in accuracy from 60% to 88%. The benefits of using US were greater when pleural effusion was present versus absent (OR, 10.8 versus 2.4) and when examining older versus younger patients (OR, 10.2 versus 2.8). Conclusions: These results demonstrate that medical students' ability to detect the presence or absence of pleural effusion is superior when using lung US as an adjunct to the physical examination than when using the physical examination alone.